Extraction and Characterization of 2-Isopropenyl-1-methoxy-7, 7-dimethyl-4, 9-imidazo-5-hydroxy pyrimidine called Alchorneinol from root bark of Alchornea hirtella used for the treatment toothache, and diarrhoea is Sierra Leone - Koroma, Lahai; Kamara, L. M.; Freezer-Williams, Ronnie (SAINSMAT: Journal of Applied Sciences, Mathematics, and Its Education, 2021)
A new compound LK001 identified as 2-Isopropenyl-1-methoxyl-7, 7-dimethyl-4, 9-imidazo-5-hydroxy pyrimidine and named Alchorneinol has been extracted from the root bark of Alchornea hirtella plant. It was isolated using solvent-solvent extraction method from the powdered root bark of A. hirtella. The white powdered compound was slightly soluble in water, ethanol chloroform and tested positive for unsaturation. The compound LK001 contained Carbon, Hydrogen, Oxygen, and Nitrogen during elemental analyses. It also tested positive for the presence Hydroxide group thus making it slightly different from the already reported drug Alchorneine. The fragmentation patterns proposed from the Mass spectrum for Sample LK001 and by McLafferty rule support a new compound named Alchorneinol in the root bark extract. Itis therefore one of the active compounds responsible for the treatment of pain, particularly tooth ache, as purgative, stomach-ache and to treat tiredness after intoxication in Sierra Leone.